JENIS DAN POPULASI HAMA PADA TANAMAN STROBERI (Fragaria x ananassa Duscesne) - Kessek, Lanny I.M.; Tulung, M.; Salaki, Ch. L. (EUGENIA, 2015)
ABSTRACT Â  The study aimed to: (1) know the type of pests and predator that lived during the growth and production of strawberry plants, (2) know the populations of pests associated to the strawberry plants during vegetative and generative development stages until harvest time. The methodology used was Descriptive Method. Sampling the pests associated to strawberry plants was taken by the Method of Deliberate (Purposive Sampling Method). In the vegetative stage, the plants were in 2-10 weeks after planting, and the generative stage of flowering plants until harvest time, or age 11-20 weeks after planting. The results showed that, the pests on strawberry plants growth and development in both vegetative and generative stages, i.e.: seven order were included in nine families, those were: order Orthoptera with Acrididae and Grylotalpidae families; order Coleoptera with Curculionidae and Chrysomelidae families; order Lepidoptera with Pyralidae families; order Diptera with Drosophilidae families; order Homoptera with Aphididea families; order Acari with Tetranychidae families, and order Mollusca. There were six types of pests which destroyed the leaves on Â the vegetative phase, i.e.: Acida turita, Locusta sp., Valanga nigricornis, Chrysocus auratus, Tetranychus sp. and Aphis sp., and a kind of destructive root, that was Gryllotalpha sp. There were 11 types of pests in the generative phase, consisted of: a) six pest species destroyed the leaf, i.e.: Acida turita, Locusta sp., Valanga nigricornis, Chrysocus auratus, Tetranychus sp., and Aphis sp.; b) two kinds of fruit pests, those were : Drosphila sp. and Filicaulis bleekeri, c) as well as a type of root pest was Gryllotalpha sp. Keywords : population type and plant pests and predators; strawberry plants